Comparison of solvents for extraction of walnut oils: Lipid yield, lipid compositions, minor-component content, and antioxidant capacity. (August 2019) - Gao, Pan; Liu, Ruijie; Jin, Qingzhe; Wang, Xingguo
Abstract: Walnut oils were obtained using five different extraction solvents ( n- hexane, ethyl acetate, petroleum ether, Folch solution (chloroform/methanol, v: v = 2: 1) and acetone), and their lipid yield, lipid composition, minor components (tocopherols, squalene, phytosterols, and polyphenols), oxidative-stability indices, and antioxidant capacity (via DPPH, ABTS, FRAP, and ORAC assays) were analyzed and compared. It was found that ethyl acetate was the best solvent for extracting walnut lipids (68.32%), while n- hexane extraction gave comparatively lower linoleic acid (62.95%) and trilinolein contents (32.06%) and Folch extraction was suitable for extracting tocopherols (578.0 mg/kg). Although the walnut oil obtained by acetone extraction had relatively low phytosterols content (891.8 mg/kg), it had significantly higher polyphenol content (98.1 mg GAE/kg) and better antioxidant capacity than the other samples. In addition, we found that polyphenols contributed significantly to the antioxidant capacity of the walnut oil, and thus can be considered as health-promoting. This information is beneficial to the development of walnut oil for potential cosmetic use and health care applications. Highlights: Acetone is an excellent solvent for extracting walnut oil. Walnut oil extracted by acetone have potential health care and cosmetic use. Polyphenols are important index for antioxidant capacity prediction of walnut oil.